Mind games - Mehl, Nancy (Mehl, Nancy ; v. 1., 2018)
Kaely Quinn's methods may be unorthodox, but her talents as an FBI behavior analyst are impossible to ignore. When a reporter outs her as the daughter of an infamous serial killer, she's demoted to field agent and transferred to St. Louis. Then that reporter claims to have received an anonymous poem predicting a string of murders, ending with Kaely's. A body is found that fits the poem's predictions, and the FBI sends Special Agent Noah Hunter to St. Louis. Can Kaely and Noah catch the murder before anyone else-- including Kaely-- is killed? -- adapted from back cover